Prevalence of retinopathy of prematurity: a 3-year retrospective study - Patel, Aval S.; Mehta, Rishi (International Journal of Research in Medical Sciences, 2021)
Background: Retinopathy of prematurity (ROP) is a vasoproliferative disease of premature infants which leads to permanent blindness. Early screening is needed to diagnose ROP and prevent blindness. Methods: Retrospective study was conducted in 225 neonates from January 2018 to December 2020. All neonates with birth weight <2000 gm and/or gestational age <38 weeks were included. History of oxygen given to neonates and presence of sepsis in neonates was noted. The infant’s pupil were dilated. Fundus examination was done. All the data was entered in MS-Excel 2016 and analyzed by SPSS (version 19). Chi-square test was done to calculate p value. Results: Out of total of 225 neonates, 137 (60.88%) were males and 88 (39.12%) were females. The gestation age of neonates (in weeks) ranged from 25 to 40 (mean: 32.35). The birth weight of neonates (in grams) ranged from 570 to 2500 (mean: 1460). 21 (9.33%) were found to have ROP. The male neonates found with ROP were 16 (11.67%) while females were 5 (5.68%) (p>0.05). Out of 148 neonates who were given oxygen 19 (12.83%) developed ROP (odds ratio: 5.52). Out of 42 neonates who had sepsis, 2 (4.76%) developed ROP (odds ratio: 0.43). Conclusions: The prevalence of ROP was 9.33%. The prevalence is showing a decreasing trend. ROP is not affected by gender. Oxygen given to neonates is associated with greater ROP. But sepsis in neonates is not associated with development of ROP.